A criterion to justify a holomorphic function - Qi, Feng; Guo, Bai Ni (Global Journal of Mathematical Analysis, 2017)
In the paper, the authors present a criterion, free of considering differentiability and any partial derivative, to justify a holomorphic function and illustrate the criterion by several examples.